Getting To Know The Characteristics Of Waqf Institutions Through Nazhir's Performance - Ani Faujiah; Abu Yasid; Muhammad Lathoif Ghazali (Yayasan Adra Karima Hubbi, 2024)
Nazhir's performance in managing waqf is a form of improving the characteristics of the institution. For waqf, waqf candidates and the community in general should participate in analyzing the performance of a waqf institution which is an institution mandated by the community in receiving, managing and distributing waqf benefits. Getting to know the characteristics of waqf institutions through Nazhir's performance is one of the efforts to encourage waqf institutions to improve their performance in order to increase trust in the community. Through a qualitative approach trying to dig up several data ranging from literature reviews, observations and interviews to several waqf, Nazhir and the community on the profile of a waqf institution, it was found that the three elements are interrelated. So that each element has a contribution to the development of waqf.